Requirements for implementing the Green School’s initiative in Public Education Schools in Jeddah - Masrahi, Fatimah Talal; Alshareef, Norah Obaid; Alsaigh, Najah Mohammed (Journal of Educational and Psychological Sciences, 2024)
The research aimed to identify the requirements for implementing the Green Schools Initiative in public education schools in Jeddah Governorate. In order to achieve this goal, the descriptive survey approach was adopted, and the questionnaire was the appropriate research tool for collecting information. The research was applied to a sample of principals of public education schools in Jeddah for the three stages (elementary, intermediate, and secondary) amounting to (282) principals, as a stratified random sample. From the research community, which amounted to (1051) women directors. The research reached a number of results, most notably: that the requirements for applying the Green Schools Initiative in public education schools in Jeddah governorate came with two dimensions of human requirements and material requirements that are available to a large extent, and that there are no statistically significant differences at the level of significance (α≤0.05) in the average opinions. The research sample of female principals about the availability of the human and material requirements necessary for the implementation of the Green Schools Initiative in general education schools in Jeddah Governorate, due to the variables of experience and educational stage. Based on the research results, the researchers recommended the adoption of the Education Department in Jeddah Governorate, the Green Schools initiative in public education schools, the evaluation and follow-up of public education schools with regard to green practices, and the support of the Jeddah Education Department for scientific research related to green schools.